Internal Medicine Clerkship Multiple-Choice Quiz Questions - Amy Holthouser; Monica Shaw (Association of American Medical Colleges, 2009)
Abstract This resource is a question bank of 380 multiple-choice questions designed for use during an internal medicine clerkship. The questions are designed for open-book use to reinforce a recommended reading schedule during our 12-week internal medicine clerkship at the University of Louisville School of Medicine. Since the questions are used in an open-book manner, the questions require critical application of text material and are more difficult than standard student board-prep questions. The questions should adequately reinforce reading in any student-appropriate text. Questions are grouped by topic. Some questions are written to be used in concert with pictures; as the pictures were not the property of the authors, the pictures have been removed and a one-line description of an appropriate image substituted. Some of the questions are more ambiguous than what students will encounter in standard board prep materials. This has actually been helpful as it promotes reading from various sources and studies. However, to be able to accurately grade the quizzes, instructors should remind students that the answers can be found in their assigned texts. Correct answer choices are indicated with bold text. This resource is extremely effective in enforcing the recommended reading schedule throughout our clerkship. It has also been effective in identifying individuals at risk for self failure due either to poor test-taking skills, lack of systematic study, or inadequate background knowledge or clinical exposure. We have fewer students fail as a result of using these questions in open-book quizzes. The questions are likely too difficult to use in a closed-book quiz. Students also take a lot of time (about 4 hours) to complete each quiz.